Semantic influence of programming on the development of thinking of students: background, research and prospects - M. U. Mukasheva; Y. V. Payevskaya (Открытое образование (Москва))
Today, one of the highly discussed topics is the impact of global digitalization on the evolution of humankind. Although the widespread introduction of digital technology is considered to be effective and profitable, it requires competitive professionals, who think creatively, have necessary skills in working with modern technology, and are ready to master new knowledge, self-education, and self-development. The study is carried out as a part of the project AP05130982 “Semantic Impact of Programming on the Development of Computational Thinking of Students", which is being conducted at the National Academy of Education named after I. Altynsarin with the support of the grant from the Ministry of Education and Science of the Republic of Kazakhstan. The semantic influence of programming on the development of computational thinking implies that with continuous learning to program, that requires high level of abstraction and logic, repetition of experimental verification actions (automatism), visual representation of results, and the work with the elimination of syntactic and logical errors have a significant impact on the development of students’ mental abilities.Purpose is to study the semantic influence of knowledge and programming skills on the development of secondary school students’ computational thinking in the context of programming training.Materials and methods. The scientific and methodological basis of the research are: the provision on the zone of proximal development in the theory of activity (L. Vygotsky), principles of the theory of thinking (J. Piaget, J. Bruner), the concept of learning on micro worlds, which represent some models of the real world (S. Papert), elements of the theory of computation, theory of algorithms and programming (D. Fink, D. Knut, N. Wirth and others).The empirical data on the study of the semantic influence of programming on the development of mental abilities of primary school students in the process of learning programming (Scratch) were obtained using a specially developed technique (framework) for studying the dynamics of the development of computational thinking. This method is developed on the basis of a tiered approach to assessing the acquisition of knowledge and information (B. Bloom, V. Bespalko).The study used general scientific methods of analysis and synthesis, generalization, abstraction, methods of grouping and classification of data, and statistical methods.Results. A generalized structural interpretation of computational thinking and a hypothetical model of the semantic influence of programming on the development of computational thinking of students in schools have been developed.Preliminary conclusions were drawn that the level of digital competence of a modern teacher, his ability to integrate useful knowledge and interdisciplinary skills in the global information and educational space, as well as ensuring the continuity of the learning process, are ofparticular importance in the process of creating modern digital skills that contribute to the development of computational thinking at all levels of education.Conclusion. It is assumed that the results of the study of computational thinking (a generalized interpretation structure, a hypothetical model of the semantic influence ofprogramming, a framework for assessing levels) will contribute to a systematic and comprehensive study of many aspects of the development of computational thinking.